Social reintegration of individuals convicted of terrorism in France: From paradox to blind spot? - Amadio, Nicolas (European journal of probation, 2024)
Social reintegration of individuals convicted of terrorism is a major issue of probationary and scientific debate. However, while the issue has made significant strides internationally, it has until now received little attention in France. The aim of this article is to highlight this difference in interest and to provide some insights into the reasons for this. It does this by drawing on a literature review of French scientific articles published in peer-reviewed journals between 2012 and 2022. The article first defines the notion of social reintegration. Then, it highlights how, while the question of réinsertion of prisoners is presented as a fundamental objective of probationary practices and is a subject of interest in French research, the same cannot be said for social reintegration. This article concludes that this difference can be explained in terms of the interplay between practical and academic fields, internationalization, and interdisciplinarity.